Dynamic auroral storms on Saturn as observed by the Hubble Space Telescope. Issue 10 (20th May 2014) - Nichols, J. D.; V.Badman, S.; Baines, K. H.; Brown, R. H.; Bunce, E. J.; Clarke, J. T.; Cowley, S. W. H.; Crary, F. J.; Dougherty, M. K.; Gérard, J.‐C.; Grocott, A.; Grodent, D.; et al.
Abstract We present observations of significant dynamics within two UV auroral storms observed on Saturn using the Hubble Space Telescope in April/May 2013. Specifically, we discuss bursts of auroral emission observed at the poleward boundary of a solar wind‐induced auroral storm, propagating at ∼330% rigid corotation from near ∼01 h LT toward ∼08 h LT. We suggest that these are indicative of ongoing, bursty reconnection of lobe flux in the magnetotail, providing strong evidence that Saturn's auroral storms are caused by large‐scale flux closure. We also discuss the later evolution of a similar storm and show that the emission maps to the trailing region of an energetic neutral atom enhancement. We thus identify the auroral form with the upward field‐aligned continuity currents flowing into the associated partial ring current.